Antecedents of e-government perceived net benefits: a study of e-filing in Indonesia - Raniasa Putra; Kiagus Muhammad Sobri; Azhar Azhar; Anang Dwi Santoso (Universitas Ahmad Dahlan, 2022)
Given that electronic filing is one of the earliest e-government services in Indonesia, additional research is needed to determine the antecedents of service users’ perceived net benefit. The e-government system success model by DeLone and McLean was used in this study, however trust factors were added to the government, technology, and e-government websites as antecedents. 195 individual taxpayers were sent a questionnaire including 39 statements as part of the study examination. Data were analyzed using structural equation model-partial least square (SEM-PLS) with the assistance of WarpPLS. This study concludes that these three antecedents determine the success of the e-government system, and thus that e-government development is the integration of trust in government, which is built by increasing its credibility in the eyes of the public, trust in technology, which can be accomplished through education, and trust in e-government websites, which can be accomplished by consistently improving the security and quality of government website services.